Joint Sale Scheme for Credit Settlement After POJK 48: Skema Penjualan Bersama untuk Pelunasan Kredit Pasca POJK 48 - Mohammad Wildan Habibi; Sri Budi Purwaningsih (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Credit settlement plays a crucial role in maintaining financial system stability, especially when non-performing loans increase during economic disruptions. Specific Background Following the COVID-19 pandemic, banks implemented restructuring policies under POJK No. 48 of 2020, including alternative settlement mechanisms such as the Joint Sale and Purchase scheme at Bank X. Knowledge Gap However, limited studies examine the legal status and practical implementation of this scheme in post-restructuring credit settlement. Aims This study aims to analyze the special policy of Joint Sale and Purchase and its legal consequences for debtors in resolving non-performing loans at Bank X. Results The findings show that the scheme allows debtors to sell collateral independently within a specified period, ensuring optimal asset value while maintaining creditor rights, and if unsuccessful, the bank proceeds with auction or cessie mechanisms. Novelty This study highlights the structured integration of restructuring policies with non-litigation credit settlement through a collaborative asset disposal mechanism. Implications The results suggest that this scheme provides a practical legal framework for balancing debtor flexibility and creditor protection in post-pandemic credit management. Keywords: Credit Settlement, Joint Sale Scheme, Bank Policy, Non Performing Loan, POJK 48 Key Findings Highlights Debtors are given a limited period to dispose collateral independently Settlement prioritizes principal repayment before other obligations Follow-up actions include auction or cessie after deadline